Effect of oxybutynin patch versus mirabegron on nocturia‐related quality of life in female overactive bladder patients: A multicenter randomized trial. (29th May 2021) - Suzuki, Toshiro; Minagawa, Tomonori; Saito, Tetsuichi; Nakagawa, Tatsuo; Suzuki, Tomio; Furuhata, Masayuki; Hosaka, Kyoko; Ogawa, Teruyuki; Ishizuka, Osamu
Abstract : Objectives: To investigate the effect of oxybutynin patch versus β3‐adrenoceptor agonist mirabegron on nocturia‐related quality of life in female overactive bladder patients. Methods: In the present study, female overactive bladder patients were enrolled. The patients were randomly allocated into two groups: the oxybutynin patch group and the mirabegron group. Each of the drugs was given for 8 weeks. The changes in the total Nocturia Quality of Life Questionnaire score were evaluated. Parameters on a frequency volume chart were also evaluated. Results: In total, 100 patients (51 oxybutynin patch, 49 mirabegron) were treated with oxybutynin patch or mirabegron. The changes in the Nocturia Quality of Life Questionnaire score 4 weeks after administration were 3.8 ± 18.6 and 8.7 ± 13.1 with the oxybutynin patch group and the mirabegron group, respectively, which were significantly higher than those at the baseline. Furthermore, the changes in the Nocturia Quality of Life Questionnaire score 8 weeks after administration were 4.3 ± 16.5 and 7.7 ± 12.3, respectively. A statistical difference was seen only in the mirabegron group. Regarding the Nocturia Quality of Life Questionnaire subscores, oxybutynin patch and mirabegron significantly improved the Nocturia Quality of Life Questionnaire bother/concern subscore 4 and 8 weeks after administration, whereas the Nocturia Quality of Life Questionnaire sleep/energy subscore was not significantly improved in each period. Eight weeks after administration, 24‐h frequency, 24‐h urinary urgency and mean voided urine volume were improved in both groups statistically. Conclusions: The oxybutynin patch improves quality of life, focusing mainly on nocturia by improving the bother/concern subscores of the Nocturia Quality of Life Questionnaire in the short term.